Activity preferences of Gen Z in rural communities: key insights for improving the Philippine PATH-Fit program - Tagare, Jr., Ruben L.; Saroca, Jr., Daniel B.; Aguinaldo, Jerrwin C.; Dagoc, Priscilla P.; Sumera, Eduard S.; Mancera, Marlon A.; Esto, Jomar B.; Janito, Cheeze R.; Orfrecio, Marlene E.; Elumbaring, Jerum B. (Intelektual Pustaka Media Utama, 2026)
This study explored the activity preferences of Generation Z (Gen Z) students in rural communities to enhance the implementation of the Philippine physical activity towards health and fitness (PATH-Fit) program. Utilizing a qualitative-ethnographic approach, insights were obtained from 20 selected Gen Z students through expert-validated open-ended questions. The findings highlighted seven key preferences: lessen the lectures, holistic activities, sports and physical activities, comfort, accessibility, and convenience, community and outdoor activities, activities to deviate from technology, and activities that do not add stress. The study revealed that Gen Z students in rural areas prefer PATH-Fit activities that are engaging, diverse, and supportive of their overall well-being. They favor fewer lectures to allow for more interactive learning experiences that integrate social, mental, and emotional aspects alongside physical activities. Additionally, they seek activities that are comfortable, accessible, and convenient, valuing easy access and minimal hassle. Community engagement and outdoor experiences are also crucial to them, as are opportunities to disconnect from technology and avoid stress. These preferences emphasize the need for a well-rounded and adaptable approach to physical education (PE) that aligns with Gen Z students’ diverse needs and well-being in rural communities.